Influence of supplemental protein versus energy level on intake, fill, passage, digestibility, and fermentation characteristics of beef steers consuming dormant bluestem range forage - T. DelCurto; B. Cochran; T. Avery; A. Beharka (Kansas Agricultural Experiment Station Research Reports, 1988)
Two trials were conducted to evaluate effects of protein versus energy level in milo/soybean meal supplements on intake and utilization of dormant, bluestem forage. Forage dry matter intake and utilization of dormant bluestem forage appears to increase at higher levels of supplemental protein. Increased supplemental energy may be associated with depressed intake and utilization, particularly when supplements are low in protein.
Keywords: Kansas Agricultural Experiment Station contribution; no. 88-363-S; Cattlemen& #x27; s Day; 1988; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 539; Beef; Protein vs energy; Steers; Dormant bluestem range forage; Intake; Fill; Digestibility; Fermentation